2021
DOI: 10.3390/s21144849
|View full text |Cite
|
Sign up to set email alerts
|

Design of Grating Al2O3 Passivation Structure Optimized for High-Efficiency Cu(In,Ga)Se2 Solar Cells

Abstract: In this paper, we propose an optimized structure of thin Cu(In,Ga)Se2 (CIGS) solar cells with a grating aluminum oxide (Al2O3) passivation layer (GAPL) providing nano-sized contact openings in order to improve power conversion efficiency using optoelectrical simulations. Al2O3 is used as a rear surface passivation material to reduce carrier recombination and improve reflectivity at a rear surface for high efficiency in thin CIGS solar cells. To realize high efficiency for thin CIGS solar cells, the optimized s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…143 Al 2 O 3 is also usually used as a passivation layer in CIGS and Si-based solar cells. 144,145 It was reported that Fe 2 O 3 intended to serve as an ETL could also play the passivation layer role in perovskite solar cells. The Fe 2 O 3 ETL layer in the form of nanoparticles having network morphology could improve the cell performance induced by the passivation effect of interface defects and thus generated a high UV stability.…”
Section: Rf Sputteringmentioning
confidence: 99%
See 1 more Smart Citation
“…143 Al 2 O 3 is also usually used as a passivation layer in CIGS and Si-based solar cells. 144,145 It was reported that Fe 2 O 3 intended to serve as an ETL could also play the passivation layer role in perovskite solar cells. The Fe 2 O 3 ETL layer in the form of nanoparticles having network morphology could improve the cell performance induced by the passivation effect of interface defects and thus generated a high UV stability.…”
Section: Rf Sputteringmentioning
confidence: 99%
“…Various metal oxides were found suitable to serve as a passivation layer in many solar cell devices. , For instance, organic solar cells with triethanolamine-passivated ZnO exhibited a very minimum trap density and thus increased electron mobility and induced longer times in charge carrier recombination lifetime; consequently, the PCE improved . Al 2 O 3 is also usually used as a passivation layer in CIGS and Si-based solar cells. , It was reported that Fe 2 O 3 intended to serve as an ETL could also play the passivation layer role in perovskite solar cells. The Fe 2 O 3 ETL layer in the form of nanoparticles having network morphology could improve the cell performance induced by the passivation effect of interface defects and thus generated a high UV stability …”
Section: Fabrication and Required Development Of Iron Oxides For Sola...mentioning
confidence: 99%
“…On the other hand, the EM wave interaction with the line contact architecture promotes changes in the electric field distribution, since the periodic line grating will influence the interference pattern, disrupting the previously seen planar behavior. In this case, at 1036 nm the presence of a HPS promotes for a destructive interference that increases with increased SiO2 thickness, as more light is reflected with the thicker layer [54]. An optical optimization of the HPS architecture is required in order to shift the destructive interference away from the solar spectrum region of interest (> 1100 nm).…”
Section: A Optical Simulationsmentioning
confidence: 99%
“…The average reflectance of a TJ solar cell is decreased from 25.57 to 3.37 % thanks to TLAR coating, which has a stronger antireflection effect in the wavelength range of 300 -1,800 nm than TiO2/Al2O3 DLAR coating [17]. Using optoelectrical simulations, Wang improved the structure of thin Cu(In,Ga)Se2 (CIGS) solar cells with a grating aluminium oxide (Al2O3) passivation layer (GAPL) offering nano-sized contact holes [18]. The efficient carrier recombination inhibition and high reflectivity of the Al2O3 insulator passivation with local contacts caused the efficiency value to peak at 100 nm for the contact opening width [18].…”
Section: Introductionmentioning
confidence: 99%
“…Using optoelectrical simulations, Wang improved the structure of thin Cu(In,Ga)Se2 (CIGS) solar cells with a grating aluminium oxide (Al2O3) passivation layer (GAPL) offering nano-sized contact holes [18]. The efficient carrier recombination inhibition and high reflectivity of the Al2O3 insulator passivation with local contacts caused the efficiency value to peak at 100 nm for the contact opening width [18].…”
Section: Introductionmentioning
confidence: 99%